Nitrogen and magnesium foliar fertilization in soybean and maize - Rodrigues, Vitor Alves (2021)
Soybean [Glycine max L. (merr.)] and maize (Zea mays L.) are the most important crops grown in cultivated area in Brazil. With the increasing demand for food, without increasing the area destined for agriculture, it is necessary to adopt technologies to increase yield and one of these technologies is foliar fertilization, which promote a stimulant effect, it is a tool that can contribute to minimize adverse environmental effects, such as water stress, high temperatures and solar radiation. Thus, the objective of this work was evaluate the physiological effects of foliar application of nitrogen and magnesium in soybean and corn in two growing seasons, splitting in two chapters. In the first chapter a study was carried out with foliar nitrogen in soybean in 2018/2019 and 2019/2020 growing seasons, and in corn 2019 and 2020 growing seasons. Second chapter refers to the study with magnesium in the same crops and growing season as in chapter 1. The experiments were carried out in the field at Lageado Experimental Farm belonging to the College of Agricultural Sciences of the São Paulo State University. Applications occurred in R3 and V10 physiological stages for soybean and corn, respectively. The evaluations carried out in both experiments were the nutritional plants status, gas exchange paramters, photosynthetic enzymes (Rubisco for soybean and Rubisco and PEPcase for corn), total soluble sugar concentration, oxidative stress and oxidative enzymes (hydrogen peroxide, malondialdehyde, superoxide dismutase, catalase, ascorbate peroxidase and proline content), estimation of number of grains per plant, 100-grain weight and grain yield. Foliar N provided increased net photosynthesis, stomatal conductance, water use efficiency and carboxylation. The application foliar Mg contributed to increase antioxidative enzymes, reduce oxidative stress and improve the of the accumulated energy of photosynthesis. The results obtained in this research represent a good strategy to decrease the stress caused by abiotic factors and increase the crop yield.